2022
DOI: 10.1071/an21535
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of corticosterone in the plasma, eggs and faeces of laying hens

Abstract: Context Stress responses in chickens are commonly assessed from measurements of corticosterone in blood, but there is an increasing research effort to develop non-blood means of assessing the activity of the hypothalamo–pituitary (HPA) axis. It is common to measure corticosterone in the eggs and faeces. Aims We extended previous work by undertaking a study of caged laying hens comparing basal concentrations of corticosterone in plasma, faeces, egg albumen and egg yolk on a between-cage basis. We tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Indeed, corticosterone was elevated in laying hens raised under suboptimal conditions including high stocking density, heat stress, or immune suppression ( Najafi et al, 2015 ; Nawab et al, 2020 ). Per the positive relationships between corticosterone concentration in eggs and blood samples ( Engel et al, 2022 ), our finding might indicate that laying hens fed on low CP diets were in a less stressed state. On the contrary, Lee et al (2016) reported that low CP diets (18 vs. 19% CP in diets) tended to increase serum concentration of corticosterone in broiler chickens.…”
Section: Discussionmentioning
confidence: 68%
“…Indeed, corticosterone was elevated in laying hens raised under suboptimal conditions including high stocking density, heat stress, or immune suppression ( Najafi et al, 2015 ; Nawab et al, 2020 ). Per the positive relationships between corticosterone concentration in eggs and blood samples ( Engel et al, 2022 ), our finding might indicate that laying hens fed on low CP diets were in a less stressed state. On the contrary, Lee et al (2016) reported that low CP diets (18 vs. 19% CP in diets) tended to increase serum concentration of corticosterone in broiler chickens.…”
Section: Discussionmentioning
confidence: 68%
“…Hormones in egg can lead to changes in phenotype which influences physiology, behavior, and morphology ( Peixoto et al, 2020a ; Oluwagbenga et al, 2023a ). GC deposition in egg has been reported ( Love et al, 2008 ; Okuliarová et al, 2010 ; Caulfield and Padula, 2020 ; Engel et al, 2022 ; Oluwagbenga et al, 2023b ) and an increase in deposition has been reported following HS in laying hens ( Downing and Bryden, 2008 ; Kim et al, 2022a ), Japanese quails ( Pu et al, 2019 , 2020 ), and ducks ( Oluwagbenga et al, 2022 ).…”
Section: Introductionmentioning
confidence: 97%